Optimization of Herpes Virus Infection Treatment in Children - Yu.P. Kharchenko; T.G. Podgornaya; N.B. Kirpichova; N.V. Dombrovskaya; A.G. Shapovalov (Zaslavsky O.Yu., 2012)
The clinical features of human herpes virus 6 in acute, latent and persistent forms at 54 children aged from 2 months to 10 years were investigated. There was revealed the polymorphism of human herpes virus 6 in children associated with virus replication activity. The important role of chronic human herpes virus 6 in forming of sickly children group with involvement of nervous and cardiovascular systems and presence of the various clinical variants correlating with the form of an infection contamination is confirmed. Principles of stratification of patients, diagnostic and treatment approaches with account of clinical semiology and complex of molecular-genetic, serological, bacteriological, neurofunctional and cardiovascular examinations were developed. The treatment positive results allow to confirm the benefit from integrative multidisciplinary therapy.